Adsorption characteristics of lead, copper, cadmium, methylene blue, phenol, and toluene in water using composite synthesized from titanium dioxides and carbon spheres through hydrothermal method. (December 2022) - Ade, Imas Agusningtyas; Tran, Hai Nguyen; Zhang, Jin-Wei; Wang, Yu-Chun; Dat, Nguyen Duy; Nguyen, Dong Thanh; Chao, Huan-Ping
Abstract: Titanium nanotubes (TNT) are commonly synthesized from TiO2 P25 under hydrothermal reaction (HTR) using 10 M NaOH). Composite adsorbents derived from TiO2 and carbon spheres (CS) were synthesized via a facile two-stage HTR process. CS was firstly synthesized from glucose through HTR. The mixture (CS, TiO2, and NaOH) was then transferred to a Teflon-lined autoclave for another HTC process to generate TNT/CS. The TNT/CS composite was calcined from 300 to 800 °C to evaluate the changes in its surface properties (functional group, morphology, and external charge), textural parameters, crystallinity, cation exchange capacity, and adsorption capacity. Results indicated that the Brunauer–Emmett–Teller surface area and total pore volume of composites were 25.0–131.9 m 2 /g and 0.099–0.33 cm 3 /g, respectively. The composites exhibited a negatively charged surface within pH 4.0–9.0, with their zeta potentials at pH 5.0 ranging from −54.60 to −31.1 mV. The result of X-ray photoelectron spectroscopy demonstrated that the main components (%atomic) in the composites were carbon (29.07%–60.75%), oxygen (29.09%–49.16%), titanium (2.93%–17.52%), and sodium (0.56%–9.48%). During the preparation of TNT/CS, CS (its negatively charged surface) can well absorb Na + ions in the mixture. This phenomenon prevented the performance of tubular morphology in TNT/CS. The synthesized composites were regarded as multifunctional adsorbents for adsorbing various contaminants (Pb 2+, Cd 2+, Cu 2+, cationic methylene blue dye, phenol, and toluene) in water. Equilibrium adsorption at pH 5.0 was carried out to estimate their adsorption capacities toward the selected contaminants. The Langmuir maximum adsorption capacities of Pb, Cd, Cu, methylene blue, phenol, and toluene were 534, 518, 514, 690, 329, 138 mg/g for TNT/CS and 334–523, 384–477, 297–453, 394–677, 303–416, 118–260 mg/g for the calcinated TNT/CS composites, and 26.3, 23.8, 21.4, 285, 239, 188 mg/g for commercial activated carbon, respectively. The adsorption mechanisms were elucidated based on the adsorption experiments and surface characteristics of TNT/CS. Ion exchange was the primary adsorption mechanism for the test cationic contaminants. The van der Waals force was an important adsorption mechanism for phenol and toluene. The developed TNT/CS composite can be employed as an effective adsorbent for adsorbing cationic and non-ionic contaminants in aqueous solutions. Graphical abstract: Unlabelled Image Highlights: New composite adsorbents derived from titanate nanotubes and carbon sphere synthesized Effect of calcination temperatures on the characteristics of composite evaluated Composite well adsorbed toxic metals (Pb, Cd, Cu), cationic dye, phenol, and even toluene Their adsorption capacity to the selected adsorbates estimated by adsorption isotherm Primary adsorption mechanism: ion exchange (for cationic compounds) and van der Waals force (non-ionic ones)